STYLISTICS OF LAUGHTER: EXPLORING COMIC LANGUAGE IN THE FICTION OF LEACOCK, TWAIN, AND NARAYAN - G. BANAZEER BANU; Dr.S.GUNASEKARAN (The Bioscan, 2025)
Humour, as a powerful mode of cultural and linguistic expression, plays a pivotal role in literature. The works of Stephen Leacock, Mark Twain, and R.K. Narayan stand as prominent examples of how language can be intricately used to evoke laughter while also delivering sharp social commentary. This study, titled "Stylistics of Laughter: Exploring Comic Language in the Fiction of Leacock, Twain, and Narayan", is motivated by the need to understand how comic vision is linguistically constructed across different cultural contexts. The choice of these three authors—representing Canadian, American, and Indian literary traditions—enables a cross-cultural investigation of humour through stylistic and linguistic frameworks. The research is grounded in stylistic theory, particularly the principles of linguistic foregrounding, pragmatic incongruity theory, and discourse analysis. These theories provide a systematic lens to examine how humour functions through wordplay, irony, narrative voice, and syntactic structures. The primary objectives of this study are to identify the distinctive linguistic techniques used to generate humour, to compare their stylistic patterns, and to evaluate how cultural contexts shape their comic narratives. The research employs a qualitative methodology based on close textual analysis of selected short stories and narrative episodes from the three authors. Elements such as figurative language, irony, dialogue, code-switching, and narrative tone are critically examined. The findings reveal that while Leacock leans heavily on absurdity and parody, Twain employs dialect-based humour and satire rooted in American socio-political realities. Narayan, on the other hand, integrates subtle irony and culturally embedded linguistic humour. Despite their geographical and cultural differences, all three writers use stylistic devices that foreground humour to critique societal norms, human folly, and everyday life. This study highlights the universality of humour and affirms the value of stylistic analysis in uncovering the linguistic artistry behind literary comedy.